Enhanced production of multi-strange hadrons in high-multiplicity proton-proton collisions - Adam, J.; Adamov, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; et al. (Nature Publishing Group, 2017)
At sufficiently high temperature and energy density, nuclear matter undergoes a transition to a phase in which quarks and gluons are not confined: the quark–gluon plasma (QGP)¹. Such an exotic state of strongly interacting quantum chromodynamics matter is produced in the laboratory in heavy nuclei high-energy collisions, where an enhanced production of strange hadrons is observed²⁻⁶. Strangeness enhancement, originally proposed as a signature of QGP formation in nuclear collisions⁷, is more pronounced for multi-strange baryons. Several effects typical of heavy-ion phenomenology have been observed in high-multiplicity proton–proton (pp) collisions⁸⁻⁹ , but the enhanced production of multi-strange particles has not been reported so far. Here we present the first observation of strangeness enhancement in high-multiplicity proton–proton collisions. We find that the integrated yields of strange and multi-strange particles, relative to pions, increases significantly with the event charged-particle multiplicity. The measurements are in remarkable agreement with the p–Pb collision results¹⁰,¹¹ indicating that the phenomenon is related to the final system created in the collision. In high-multiplicity events strangeness production reaches values similar to those observed in Pb–Pb collisions, where a QGP is formed.
Keywords: Physics; Strangeness production; Strangeness; Quark–gluon plasma; Nuclear physics; Hadron; Particle physics; Strange quark; Pion; Multiplicity (mathematics); Baryon; Strange matter; Nuclear matter; Quantum chromodynamics; Quark; Phase transition; Nucleon; https://purl.org/pe-repo/ocde/ford#1.06.00